РЕГУЛЯРНІСТЬ ТА ІНТЕНСИВНІСТЬ ТУРИСТИЧНИХ ПОТОКІВ У МІЖНАРОДНОМУ ТУРИЗМІ В ПЕРІОД 2005-2018 РОКІВ (НА ПРИКЛАДІ ЧЕРНІВЕЦЬКО ОБЛАСТІ) - Костащук, Володимир Іванович (Одеський національний університет імені І.І. Мечникова, 2020)
Problem Statement and Purpose However, quantitative (number of tourists, cost of tourist trips) indicators do not fully reflect the formation of international tourist flows. Therefore, in this work it is proposed to investigate the regularity and intensity of tourist flows between Chernivtsi oblast and countries of the world. It is suggested to use appropriate coefficients to estimate these indicators. Data & Methods. By regularity of tourist flows we mean that there are certain tourist connections during the period under study. In order to determine this indicator, it is proposed to use the coefficient of regularity of international tourist exchanges (Кs). One of the most important aspects of international tourism development between the countries of the world is the study of the intensity of tourist exchanges. It is understood as the number of tourist trips made between counties during some time (for this study, 1 day). To determine the intensity of tourist exchanges, we propose to calculate the intensity index of international tourist exchanges (Іі). Results The calculation of the indicators of the coefficient of regularity of international tourist connections (Кs) shows that during the years 2005-2018, various indicators of the regularity of tourist exchanges can be traced. The regular tourist connections between Chernivtsi oblast and the countries of the world are characteristic for 35 countries, that makes 30.95% of the total number of countries with which international tourist exchanges are registered in the oblast. An important aspect of the study of international tourism is the study of the intensity of tourist flows between countries. According to the intensity index of international tourist exchanges, all countries of the world are divided into 9 groups.
REGULARITY AND INTENSITY OF TOURIST FLOWS IN INTERNATIONAL TOURISM AT THE BEGINNING IN THE PERIOD 2005-2018 (ON THE EXMPLE OF CHTRNIVTSI OBLAST)
Keywords: international tourism, international tourist flows, regularity of tourist exchanges, intensity of international tourist. міжнародний туризм, міжнародні туристичні потоки, регулярність туристичних обмінів, інтенсивність міжнародних туристичних обмінів. exchanges.